2006
DOI: 10.1016/s0022-5347(05)00418-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Confidence and Relationship Satisfaction of Men With Erectile Dysfunction Treated With Sildenafil Citrate: A Multicenter, Randomized, Parallel Group, Double-Blind, Placebo Controlled Study in the United States

Abstract: In this study of men with ED, sildenafil produced substantial improvements in self-esteem, confidence and relationship satisfaction as measured by SEAR scores, which showed moderate to high positive correlations with IIEF scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 16 publications
5
74
0
2
Order By: Relevance
“…10,14,19 The erectile function domain of the IIEF had the strongest correlation with all SEAR components in all studies. Conversely, the sexual desire domain of the IIEF had the weakest correlation with all SEAR components in all studies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…10,14,19 The erectile function domain of the IIEF had the strongest correlation with all SEAR components in all studies. Conversely, the sexual desire domain of the IIEF had the weakest correlation with all SEAR components in all studies.…”
Section: Discussionmentioning
confidence: 82%
“…8 Since its development, the treatment responsiveness of the SEAR questionnaire has been demonstrated in two clinical trials, based in the United States, of sildenafil citrate in men with ED. [9][10][11] Since the development and validation of the English version, the SEAR questionnaire has been linguistically translated into other languages, including Spanish. 12 The SEAR questionnaire consists of 14 questions divided into two domains: the sexual relationship domain (eight items) and the confidence domain (six items).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the placebo group, the group treated with sildenafil (n ¼ 128) had greater improvements Vardenafil and tadalafil have advantages over sildenafil S Doggrell in all SEAR components. 69 Another study has shown that sildenafil is associated with the normalization of relationships, confidence and self-esteem in the SEAR questionnaire in men with ED. 70 In patients who do not respond to sildenafil at 100 mg, increasing the dose increases the responders but also increases the adverse effects.…”
Section: Clinical Trials With Sildenafilmentioning
confidence: 98%
“…30 , son los primeros controlados por placebo para evaluar los cambios que se producen en la autoestima, medida por la escala SEAR, tras el tratamiento de la disfunció n eré ctil con sildenafilo.…”
Section: Discusió Nunclassified